2012
DOI: 10.1016/j.foodcont.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dietary intake and content of lead and cadmium in infant cereals marketed in Spain

Abstract: Abstract:Lead and cadmium have become highly toxic metallic elements. There is an obvious toxicological impact of these elements on infants since their intestinal absorption is significantly higher than in adults, thus it is desirable to quantify lead and cadmium levels in commonly consumed infant foods. Zeeman background correction, transversely heated graphite furnace atomic absorption spectrometry, was used to determine both the lead and cadmium content of 91 Spanish infant cereals. Cereals were assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 39 publications
2
15
1
1
Order By: Relevance
“…This fact was confirmed by high statistical significance when compared by means of a Mann-Whitney U-test (p<0.001). The same behavior is observed in previous studies on lead, cadmium and aflatoxins in the infant cereals (Hernández-Martínez, & Navarro-Blasco, 2012;. On the contrary, other reported studies suggest little difference in the arsenic content found in organic vegetables with respect to their ordinary or conventional production (Ghidini et al, 2005); only selective, occasional and sporadic contaminations may explain high levels of these contaminants (Malmauret, Parent-Massin, Hardy, & Verger, 2002).…”
Section: Influence Of Cereal Production Methods On Mercury and Arsenicsupporting
confidence: 87%
“…This fact was confirmed by high statistical significance when compared by means of a Mann-Whitney U-test (p<0.001). The same behavior is observed in previous studies on lead, cadmium and aflatoxins in the infant cereals (Hernández-Martínez, & Navarro-Blasco, 2012;. On the contrary, other reported studies suggest little difference in the arsenic content found in organic vegetables with respect to their ordinary or conventional production (Ghidini et al, 2005); only selective, occasional and sporadic contaminations may explain high levels of these contaminants (Malmauret, Parent-Massin, Hardy, & Verger, 2002).…”
Section: Influence Of Cereal Production Methods On Mercury and Arsenicsupporting
confidence: 87%
“…The results reported in Pakistan [7,27,28] indicate higher contamination of cereal-based infant foods than in Poland. Content of cadmium in other infant foods, i.e., juices, fruit-based desserts, herbal teas, and teas with the addition of fruits was lower compared with the above-mentioned infant foods.…”
Section: Cadmium Contaminationmentioning
confidence: 85%
“…Excess cadmium (Cd) can cause kidney stones, while excess lead (Pb) can affect brain activity in children [2]. Once the heavy metals such as Cd and Pb are dispersed in water, soil and air, they could be accumulated by the crops [3], [4] if groundwater is used for irrigation. Toxicity to the human kidney by chronic ingestion of uranium (U) through drinking water in the range of 0.004 to 9µg L -1 per body weight per day may produce interference with kidney functions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Once the heavy metals such as Cd and Pb are dispersed in water, soil and air, they could be accumulated by the crops [3], [4] if groundwater is used for irrigation. Toxicity to the human kidney by chronic ingestion of uranium (U) through drinking water in the range of 0.004 to 9µg L -1 per body weight per day may produce interference with kidney functions [4]. In more recent studies on humans [5], nephrotoxic effects of U in drinking water were found even for low concentrations, without a clear threshold.…”
Section: Introductionmentioning
confidence: 99%